The Potential of Greywater Utilization Through Circular Economy Approach in Urban Areas: A review - Ario Wisnu Wicaksono (Jurnal Permukiman, 2026)
The development of urban areas in Indonesia continues to accelerate in line with increasing urbanization and rapid population growth. Greywater which is domestic wastewater from activities such as bathing and washing, accounts for 60–70% of total household wastewater and holds significant potential for reuse. This paper examines the optimization of greywater utilization through a circular economy approach that emphasizes recycle, reuse, and resource efficiency. The use of greywater not only helps reduce clean water consumption and the burden on wastewater treatment systems but also supports urban irrigation, sanitation, building cooling, and fire suppression. The implementation model includes the design of greywater collection systems, treatment technologies, and distribution networks. Environmental impacts include water conservation, pollution reduction, and energy savings, while economic benefits consist of lower operational costs, increased property value, and job creation. For city-scale implementation, regulations, financial incentives, spatial planning integration, public education, and cross-sector collaboration are essential. The optimization of greywater is considered a strategic step in supporting sustainable infrastructure development and in realizing resilient and competitive cities in the future.